The historical and cultural values of the Tree of Life in the Kingdom of Bahrain - Al-Baqali, Manar; Alshamsi, Badriya (Al-Adab Journal, 2025)
Heritage has a comprehensive meaning for all that is inherited from cultures that include values, traditions, and visions, and this does not meanIt belongs only to the past, but rather it is a cultural extension that lives with the era, and has an impact on contemporary life, which makes it have an impact on political, social, cultural, and spiritual life, and increases its historical and cultural value.The study touched on the profound historical and cultural importance of the Tree of Life in the Kingdom of Bahrain. Rooted in the arid landscape of Bahrain's desert, this reclusive tree of life represents a powerful example of endurance, defying the harsh conditions surrounding it for centuries. By examining historical beliefs, folklore and cultural practices, the study illustrates the multifaceted layers of meaning attributed to this iconic natural landmark. the Tree of Life serves as a focal point of Bahraini identity, embodying themes of resilience, continuity and interconnectedness with the environment. Its presence has inspired countless historical narratives and spiritual beliefs, and has become a sacred symbol of strength and vitality in Bahrani culture. Moreover, the tree's distinctive presence has facilitated scientific research into its adaptive mechanisms, contributing to a deeper understanding of the desert environment and conservation efforts. this study emphasizes the essential relationship between nature and culture, and shows how the Tree of Life transcends its botanical significance to become a powerful symbol of heritage and tradition in the Kingdom of Bahrain. By clarifying its historical and cultural value, it will subsequently impact Bahraini society.